Operating continuity insurance of electric vehicle by using fault-tolerant control of 7-leg inverter - Aboub, Youcef; Bouchafaa, Farid; Tabbache, Bekheıra; Mekhilef, Saad; Benbouzid, Mohamed E.H.; Benlahbib, Boualam (ACTA Press, 2018)
In this paper, a new fault-tolerant control (FTC) is applied to a 7-leg inverter pulse width modulation (PWM) to control dual induction motors (IMs) driving two electric-vehicle (EV) wheels. This FTC maintains the continuity of operation case of the fault the same as in pre-fault. In a faulty condition, two legs are added to the normal condition configuration and both are connected to the IM neutrals through other switches. Therefore, the added legs are activated only when the fault has occurred. This topology allows minimizing the power switches; thus, weight, size and cost of the vehicle architecture are optimized. In this work, the fault is assumed to be known a priori and the focus is on the remedial actions upon fault occurrence. The proposed FTC is based on a PWM control strategy in parallel to independent control. It reduces power switch failure within the control system and allows a reconfigurable topology that keeps the EV performance in faulty conditions as similar as in the case of normal conditions. Experiments and simulations, regarding IMs drive on an EV, are carried out using the European urban driving cycle to demonstrate the behaviour of the suggested FTC, which provides the same performance as the pre-fault case.